The role of ion valence in the submillisecond collapse and folding of a small RNA domain - Pabit, Suzette A. (2013)
Following the addition of ions to trigger folding, RNA molecules transition from rigid, extended states to a compact ensemble. Determining the time scale for this collapse provides important insights into electrostatic contributions to RNA folding; however it can be challenging to isolate the effects of purely non-specific collapse, e.g. relaxation due to backbone charge compensation, from the concurrent formation of some tertiary contacts. To solve this problem, we decoupled non-specific collapse from tertiary folding using a single point mutation to eliminate tertiary contacts in the small RNA subdomain known as tP5abc. Microfluidic mixing with microsecond time resolution and FRET detection provides insight into the ionic strength dependent transition from extended to compact ensembles. Differences in reaction rates are detected when folding is initiated by monovalent or divalent ions, consistent with equilibrium measurements illustrating the enhanced screening of divalent ions relative to monovalent ions at the same ionic strength. Ion-driven collapse is fast and a comparison of the collapse time of the wild type and mutant tP5abc suggests that site binding of Mg(2+) occurs on submillisecond time scales.